ANALISIS KEPEMIMPINAN TRANSFORMASIONALKEPALA DINAS PENDIDIKAN DALAM PENERAPANOTONOMI PENDIDIKAN DI KOTA PALU - Imran, Imran (Katalogis, 2013)
This study investigated the transformational leadership of the Head of Education Office in the implementation of education autonomy in Palu City and the supporting and constraint factors of the implementation of education autonomy in Palu city. The theory which was used as the basis of the analysis porposed by Bass (2006) Transformational Leadership, consisting of idealized influence, inspirational stimulation and individualized consideration. The research employed qualitative method. The informan was drawn research. Sample of this study was purposively. which consisted the Head of Education Office, four head of office division, and 3 school headmasters. The data were collected through observation, interview and documentation. The data obtained then were analyzed by employing the three stages procedures: data reduction, data presentation, data verification or drawing conclusion. The results of the study showed that the transformational leadership of the Head of Education Office in the implementation of education autonomy in Palu City has run well, however there were some aspects that have not been optimally implemented. The constraint factors of education autonomy implementation were the limited budget allocated from the municipal government to support the program of educational development. The supporting factors were the adequate number of staff both terms of quality and quantity, availability of economy resources, availability of demography potency map and well managed administration organisation.